Analysis of the Process of Making Banana Chips at UD Sederhana Konda One Village, Konda District, South Konawe Regency - Ismi Rahma Yani; Dhian Herdhiansyah; Rosmawaty Rosmawaty; Asriani Asriani (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2022)
This study aims to determine the process of making banana chips UD. Simple in Konda Satu Village, Konda District, South Konawe Regency. The data was collected using observation, interviews, questionnaires, and documentation. The research analysis used descriptive analysis. The results showed that the processing of banana chips in UD. Simple begins with the stages of procuring raw materials; raw materials are obtained around the research area, namely at the Konda market and banana collectors in Konda District, then the processing of banana chips. The processing of banana chips is done by peeling or separating the fruit from the skin, slicing bananas, frying, cooling processes, and packaging banana chips. Workers two, this peeling process can take 45 minutes - 2 hours. Packaging of banana chips uses a stand-up pouch type, and one package contains 250 grams of banana chips, with the number of packages produced for one flavor variant standing at 50 packs.